The High Prevalence of Testicular Adrenal Rest Tumors in Adult Men With Congenital Adrenal Hyperplasia Is Correlated With ACTH Levels - Mazzilli, Rossella; Stigliano, Antonio; Delfino, Michele; Olana, Soraya; Zamponi, Virginia; Iorio, Cristina; Defeudis, Giuseppe; Cimadomo, Danilo; Toscano, Vincenzo; Mazzilli, Fernando (Frontiers in Endocrinology, 2019)
Introduction: The aim of this study was to determine the prevalence of testicular-adrenal rest tumors (T-ARTs) in patients with congenital adrenal hyperplasia (CAH), and to evaluate the related ultrasound (US) features, hormonal profiles, and semen parameters. Therefore, we attempted to understand the potential impact of adrenocorticotropic hormone (ACTH) on the persistence or disappearance of T-ART. Methods: We conducted a longitudinal cohort study including patients with CAH who were undergoing treatment with cortisone and, when indicated fludrocortisone replacement therapy. We performed andrological examinations, US of the testis, hormone profiling, and semen analysis. Results: Of the 25 patients (mean±SD age, 32.2±7.5years), T-ARTs were detected by US in 14(56.0%) patients. The mean±SD diameter of the lesions was 13.2±6.8mm. Among 3(21.4%) patients, the lesions were observed in one testis, whereas both testes were affected in the remaining 11(78.6%) patients. The lesions were hypoechoic in 12(85.7%) patients and hyperechoic in 2 (14.3%). Plasma ACTH and 17-hydroxyprogesterone (17-OHP) levels were significantly higher in patients with T-ART than in patients without lesions (319.4±307.0pg/mL and 12.4±2.7ng/mL versus 33.5±10.7pg/mL and 8.2±1.8ng/mL, respectively; p<0.01). The mean value of sperm concentration and motility were significantly lower in patients with T-ART than in patients without lesions (12.1±12.4x106cells/mL and 18.4±11.1% versus 41.5±23.2x106cells/mL and 30.8±15.4%, respectively; p<0.05). Logistic regression analysis showed ACTH level as a significant predictor of T-ART (p<0.05). In patients with T-ART, the dose of hydrocortisone was increased by ~25–30%, while the fludrocortisone treatment remained unchanged. After 6 months of steroid treatment, patients underwent US and hormonal evaluation. Disappearance and a reduction inT-ART was observed in 6(42.9%) and 5(35.7%) patients, respectively; a reduction in ACTH levels (from 319.4±307.0 to 48.1±5.1pg/mL; p<0.01) was reported. A significant correlation between ACTH levels reduction and T-ART diameters reduction was observed (p<0.5;r=0.55). Conclusions: T-ARTs were detected in 56% of patients with CAH and were associated with impaired semen parameters. However, these lesions are potentially reversible, as demonstrated by the disappearance/reduction after adjustment of cortisone therapy and by the reduction in plasma ACTH level. Our study supports the importance of periodic US evaluation and maintenance of plasma ACTH levels within the normal range in men with CAH.